Genes adopt non‐optimal codon usage to generate cell cycle‐dependent oscillations in protein levels - Frenkel‐Morgenstern, Milana; Danon, Tamar; Christian, Thomas; Igarashi, Takao; Cohen, Lydia; Hou, Ya‐Ming; Jensen, Lars Juhl (Molecular systems biology, 2012)
The cell cycle is a temporal program that regulates DNA synthesis and cell division. When we compared the codon usage of cell cycle‐regulated genes with that of other genes, we discovered that there is a significant preference for non‐optimal codons. Moreover, genes encoding proteins that cycle at the protein level exhibit non‐optimal codon preferences. Remarkably, cell cycle‐regulated genes expressed in different phases display different codon preferences. Here, we show empirically that transfer RNA (tRNA) expression is indeed highest in the G2 phase of the cell cycle, consistent with the non‐optimal codon usage of genes expressed at this time, and lowest toward the end of G1, reflecting the optimal codon usage of G1 genes. Accordingly, protein levels of human glycyl‐, threonyl‐, and glutamyl‐prolyl tRNA synthetases were found to oscillate, peaking in G2/M phase. In light of our findings, we propose that non‐optimal (wobbly) matching codons influence protein synthesis during the cell cycle. We describe a new mathematical model that shows how codon usage can give rise to cell‐cycle regulation. In summary, our data indicate that cells exploit wobbling to generate cell cycle‐dependent dynamics of proteins. Most cell cycle‐regulated genes adopt non‐optimal codon usage, namely, their translation involves wobbly matching codons. Here, the authors show that tRNA expression is cyclic and that codon usage, therefore, can give rise to cell‐cycle regulation of proteins. Synopsis Most cell cycle‐regulated genes adopt non‐optimal codon usage, namely, their translation involves wobbly matching codons. Here, the authors show that tRNA expression is cyclic and that codon usage, therefore, can give rise to cell‐cycle regulation of proteins. Most cell cycle‐regulated genes adopt non‐optimal codon usage. Non‐optimal codon usage can give rise to cell‐cycle dynamics at the protein level. The high expression of transfer RNAs (tRNAs) observed in G2 phase enables cell cycle‐regulated genes to adopt non‐optimal codon usage, and conversely the lower expression of tRNAs at the end of G1 phase is associated with optimal codon usage. The protein levels of aminoacyl‐tRNA synthetases oscillate, peaking in G2/M phase, consistent with the observed cyclic expression of tRNAs.